Impact of Liquidity Level on the Monetary Policy Transmission Effectiveness of the Moroccan Central Bank (Bank Al Maghrib) - Moumni, Nicolas; Nahhal, Benaissa (International Journal of Economics and Financial Issues, 2014)
In the context of international financial crisis, this paper aims to analyze the impact of the liquidity level on the monetary policy transmission effectiveness of the Moroccan Central Bank (Bank Al Maghrib, BAM). After a long period of liquidity excess, the Moroccan banking system through, since 2007, a liquidity shortage that forces BAM to inject a regular and massive quantity of liquidity. Thus, to evaluate the influence of liquidity level on the monetary policy transmission effectiveness of Bank Al Maghrib, we apply a VAR modeling over the period 1998-2012, by distinguishing the period of liquidity excess and liquidity shortage and using two types of liquidity indicators. Our results show that in an excess liquidity period the monetary policy transmission would be less efficient, especially in the longer term. Instead, a liquidity shortage situation makes it more effective. Keywords: Monetary Policy Transmission; Liquidity; VAR modeling. JEL Classifications: C5; E5